High-temperature-resistant clay-free low-solid-phase drilling fluid based on carbon nanotube filtrate reducer

Through the synergistic effect of carbon nanotube-based filter loss loss agent and ultrafine calcium carbonate, the problem of deterioration of rheology and increase of filtration loss at high temperatures of clay-free low-solid phase drilling fluid is solved, and the high-temperature salt resistance of drilling fluid is achieved and reservoir protection effect.

CN119161546AActive Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +3

Patent Information

Application Number
CN202310733114.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

The commonly used filtration loss agents in existing clay-free low-solid-phase drilling fluids are prone to fermentation and failure under high temperature conditions, resulting in poor rheology and increased filtration loss, which cannot meet the high temperature and salt resistance requirements of complex formation drilling.

Method used

Using carbon nanotube-based filter reduction agent, the polymerization of hydroxylated multi-wall carbon nanotubes with amino-containing silane coupling agent, sulfonate monomer and alkenyl polycyclic monomer is prepared to produce excellent A filter loss reducer with corrosion resistance and high heat stability, and synergistically with ultrafine calcium carbonate to form a cross-linked network structure to enhance the stability of the well wall.

Benefits of technology

It has achieved good rheology, low filtration loss, strong resistance to temperature and salt resistance at high temperatures, and good compatibility with reservoir liquids, which can effectively protect the reservoir and improve drilling efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a high-temperature-resistant clay-free low-solid-phase drilling fluid based on a carbon nanotube filtrate reducer with temperature resistance, salt resistance and filtrate reduction performance, and belongs to the technical field of oil and gas field drilling. The high-temperature-resistant clay-free low-solid-phase drilling fluid is prepared from fresh water, a pH regulator, a tackifier, a filtrate reducer, a shielding temporary plugging agent, organic salt and a deoxidant. The filtrate reducer is a filtrate reducer based on a carbon nano tube, and is a product generated by reaction of a hydroxylated multi-walled carbon nano tube, an amino-containing silane coupling agent, a sulfonate monomer, an alkenyl polycyclic monomer and a fluorine-containing short-carbon-chain acrylate monomer. The high-temperature-resistant clay-free low-solid-phase drilling fluid based on the carbon nanotube filtrate reducer has the advantages of being good in rheological property, high in temperature resistance and salt tolerance, low in system filter loss, good in compatibility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field drilling, and in particular to a carbon nanotube-based fluid loss reducer and a high-temperature resistant clay-free low-solid drilling fluid. Background Art

[0002] Clay-free low-solid drilling fluid is a drilling fluid system composed of polymer thickeners, soluble salt weighting agents, fluid loss reducers, shielding and temporary plugging agents, etc., which has good rheological properties and can protect reservoirs. The system does not contain submicron particles produced by clay minerals, and the solid content is very low. In the process of forming mud cakes during drilling circulation, the fluid loss reducers and temporary plugging agents in the drilling fluid can form a bridging transition zone on the inner wall of the wellbore, and a dense and smooth filter cake is attached to the well wall, which can reduce the filtration loss. The thickener in the drilling fluid forms a thin polymer liquid film to prevent the drilling fluid from filtering into the formation. Since the clay-free drilling fluid system has no clay solid phase, compared with the traditional drilling fluid system containing clay phase, it has low static shear force and low flow resistance, which can effectively improve the drilling speed of drilling machinery, shorten the drilling construction period, and protect the oil and gas layer.

[0003] At present, the common fluid loss reducers in clay-free low-solid drilling fluids are usually natural materials or modified products of natural materials, such as cellulose, lignin, starch and its derivatives. However, these products have weak temperature resistance and cannot meet the needs of high-temperature formation drilling. In recent years, in order to meet the needs of safe drilling in complex formation conditions, research on high-temperature and salt-resistant drilling fluid fluid loss reducers has gradually gained attention. For example, patent CN202111304142.3 discloses a high-temperature resistant and degradable solid-free drilling fluid and a preparation method thereof. The temperature resistance of the drilling fluid system is up to 180°C. The fluid loss reducer involved is modified starch, which is prepared by modification reaction of raw materials of starch, N-vinyl pyrrolidone, acrylamide, maleic anhydride and water. By introducing temperature-resistant groups (carboxyl groups, amide groups) and rigid groups (heterocyclic pyrrolidone), the rigidity and thermal motion resistance of starch are increased, and the high temperature resistance of starch is improved. Patent CN201010548957 discloses a high temperature and salt resistant, solid-free and environmentally friendly integrated drilling and completion working fluid, in which the fluid loss reducer (RYLC-II) is one or more of the quaternary graft copolymers of starch products and 2-acrylamide-2-methylpropane sulfonic acid (AMPS), N-vinyl pyrrolidone (NVP) and acrylamide (AM).

[0004] It can be seen that on the basis of cellulose, lignin, starch and their derivatives, grafted polymer monomers can improve their temperature and salt resistance to a certain extent. However, such products are prone to fermentation failure during field application, which often leads to poor rheological properties of drilling fluids and a significant increase in filtration loss.

[0005] Due to the unique physical and chemical properties of carbon nanotubes, such as superelasticity and high specific strength, they are widely used in high-performance demanding industries such as aerospace, national defense, and new energy. Currently, carbon nanotubes have also appeared in the field of drilling fluids. Patent CN202210098987.X discloses a multi-walled carbon nanotube nano-plugging agent and oil-based drilling fluid that is soft on the outside and hard on the inside. The multi-walled carbon nanotube nano-plugging agent is made of hydroxylated multi-walled carbon nanotubes (5-15nm), amino-containing silane coupling agents, diallyl urea compounds, vinylbenzene compounds containing diene bonds, long-chain acrylic compounds, and triallyl cross-linking agents. The obtained plugging agent has a particle size of 220-397nm, and its plugging performance is significantly improved compared to similar plugging agents. It is resistant to high temperatures and has little effect on the performance parameters of oil-based drilling fluids. Summary of the invention

[0006] The purpose of the present invention is to propose a carbon nanotube-based fluid loss reducer and a high temperature resistant clay-free low solid drilling fluid to achieve the advantages of good rheology, strong temperature and salt resistance, low system fluid loss, and good compatibility.

[0007] According to one aspect of the present invention, a carbon nanotube-based fluid loss reducer is provided, wherein the carbon nanotube-based fluid loss reducer is polymerized from raw materials including hydroxylated multi-walled carbon nanotubes, amino-containing silane coupling agents, sulfonate monomers, alkenyl polycyclic monomers, and fluorinated short-chain acrylate monomers.

[0008] Optionally, the amino-containing silane coupling agent is selected from any one of γ-aminopropyltrimethoxysilane (KH540), 3-aminopropyltriethoxysilane (KH550), and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560).

[0009] Optionally, the sulfonate monomer is selected from any one of sodium p-vinylbenzenesulfonate and 2-acrylamido-2-methylpropanesulfonic acid.

[0010] Optionally, the alkenyl polycyclic monomer is selected from any one of 1-vinyl-2-pyrrolidone (N-vinyl pyrrolidone), 5-vinyl-2-pyrrolidone, and 4-vinyl pyridine.

[0011] Optionally, the perfluorinated short-chain acrylic ester monomer is selected from any one of trifluoroethyl methacrylate and hexafluorobutyl methacrylate.

[0012] Optionally, the particle size of the hydroxylated multi-walled carbon nanotubes is 10 to 300 nm.

[0013] Optionally, the particle size of the carbon nanotube-based fluid loss reducer is 50 nm to 1 um.

[0014] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned carbon nanotube-based fluid loss additive, comprising the following steps:

[0015] S1: in a mixed solvent, reacting hydroxylated multi-walled carbon nanotubes with an amino-containing silane coupling agent to obtain modified multi-walled carbon nanotubes;

[0016] S2: dissolving sulfonate monomers, alkenyl polycyclic monomers, and fluorine-containing short carbon chain acrylate monomers in an aqueous emulsifier solution, and polymerizing them with the modified multi-walled carbon nanotubes under the action of an initiator to obtain a carbon nanotube-based fluid loss reducer.

[0017] Optionally, in step S1, the mass ratio of the hydroxylated multi-walled carbon nanotubes to the amino-containing silane coupling agent is 1-5:3-10.

[0018] Optionally, in step S1, the mixed solvent is ethanol and deionized water, and / or the volume ratio of the ethanol to deionized water is (3-8):(0.5-1), preferably 5:1.

[0019] Optionally, in step S2, the mass ratio of the sulfonate monomer, the alkenyl polycyclic monomer, the fluorine-containing short carbon chain monomer, and the modified multi-walled carbon nanotube is 5-10:2-5:0.5-2:1-3.

[0020] Optionally, in step S2, the emulsifier is selected from sodium dodecyl sulfate (ABS).

[0021] Optionally, the amount of the emulsifier is 0.05 to 0.1 of the total amount of monomers used, and the total amount of monomers is the total mass of sulfonate monomers, alkenyl polycyclic monomers, and fluorine-containing short-chain acrylate monomers.

[0022] Optionally, the mass ratio of emulsifier to water in the emulsifier aqueous solution is 1:(50-100).

[0023] Optionally, the initiator is potassium persulfate or azobisisobutyronitrile.

[0024] Optionally, the amount of the initiator is 0.02-0.04 of the total amount of monomers used, and the total amount of monomers is the total mass of sulfonate monomers, alkenyl polycyclic monomers, and fluorine-containing short carbon chain acrylate monomers.

[0025] Optionally, in step S1, the modification temperature is 40-60° C., and the modification time is 1-3 hours.

[0026] Optionally, in step S2, the polymerization temperature is 50-80° C., and the polymerization time is 2-6 hours.

[0027] According to another aspect of the present invention, there is provided a high temperature resistant clay-free low solid phase water-based drilling fluid, comprising the following raw materials in parts by weight:

[0028] Fresh water: 100 parts;

[0029] pH regulator: 0.2-0.5 parts;

[0030] Thickener: 1-2 parts;

[0031] Fluid loss reducer: 0.5-2 parts;

[0032] Shielding temporary plugging agent: 3 to 6 parts;

[0033] Organic salt: 20-200 parts;

[0034] Deoxidizer: 0.5-2 parts;

[0035] Wherein, the fluid loss reducer is selected from at least one of the above-mentioned carbon nanotube-based fluid loss reducer and the carbon nanotube-based fluid loss reducer prepared by the above-mentioned preparation method.

[0036] Optionally, the fluid loss reducer comprises a plurality of particle sizes, and the mass ratio of the different particle sizes is 50-100nm: 300nm-500nm: 700nm-1um=10-30: 10-40: 50-60.

[0037] Optionally, the pH adjuster is selected from one of magnesium oxide, sodium hydroxide and potassium hydroxide.

[0038] Optionally, the organic salt is selected from one or more of sodium formate and potassium formate.

[0039] Optionally, the shielding temporary plugging agent is ultrafine calcium carbonate compounded with different mesh sizes, and the different mesh sizes are calculated by mass ratio as 500-600 mesh: 1200-1500 mesh: 2000-2500 mesh = 30-60: 20-40: 10-30.

[0040] Optionally, the deoxidizer is selected from a mixture of one or more of sulfites, thioureas and citrates.

[0041] Optionally, the viscosity enhancer comprises 30 to 50 parts of xanthan gum, 10 to 30 parts of guar gum and 20 to 40 parts of vinblastine gum based on 100 parts by mass.

[0042] Carbon nanotubes can be regarded as seamless concentric cylinders formed by the curling of graphite sheets. They have excellent impact resistance, temperature resistance, corrosion resistance and other properties of graphite. They have a perfectly connected hexagonal structure and are one-dimensional molecular materials. They have a micron-level length and a nanometer-level diameter. The aspect ratio can be as high as 100 to 1000. They are a very good fiber material. Due to the large aspect ratio and specific surface area of ​​carbon nanotubes, the surface energy is high and the strong van der Waals force between carbon nanotubes makes the carbon nanotubes entangled with each other, forming disordered bundles and film structures.

[0043] Compared with the prior art, the present invention has at least the following advantages:

[0044] 1. The carbon nanotube-based fluid loss reducer provided by the present invention utilizes the stable chemical properties, good adsorption performance, excellent corrosion resistance and high thermal stability of carbon nanotubes to enhance the temperature and salt resistance of the fluid loss reducer.

[0045] 2. By grafting carbon nanotubes with polymer monomers, on the one hand, the dispersibility of the carbon nanotube fluid loss reducer in the solution is improved, and on the other hand, the temperature-resistant groups (carboxyl groups, amide groups) and rigid groups (heterocycles) are used to improve the temperature and salt resistance of the fluid loss reducer.

[0046] 3. The high temperature resistant clay-free low solid drilling fluid provided by the present invention has a low solid content, thereby reducing the damage of solid particles in the drilling fluid to the reservoir.

[0047] 4. The high-temperature resistant clay-free low-solid drilling fluid provided by the present invention utilizes the synergistic effect of carbon nanotube-based fluid loss reducers with different particle sizes and ultrafine calcium carbonate. On the one hand, the fibrous carbon nanotube-based fluid loss reducer can be filled into the gaps between the ultrafine calcium carbonate. On the other hand, the polymer monomer grafted with the carbon nanotube-based fluid loss reducer can be entangled around the calcium carbonate through chemical bonds using the hydroxyl groups on the surface of the calcium carbonate, and can form a cross-linked network structure on the well wall, thereby significantly enhancing the stability of the well wall.

[0048] 5. The fluorinated monomer grafted with the carbon nanotube filtration reducer has hydrophobic and oleophobic properties, and can form a thin hydrophobic and oleophobic polymer liquid film with the viscosity enhancer in the drilling fluid, making the mud cake formed by the drilling fluid denser and more rigid, thus slowing down the loss of the drilling fluid into the formation.

[0049] 6. The clay-free low-solid drilling fluid of the present invention has the characteristics of good high temperature resistance, with a maximum temperature resistance of 180°C. The drilling fluid system has low filtration loss after aging at 180°C for 16 hours. Formate is used as a weighting material, has good compatibility with reservoir liquid, and can improve and protect the reservoir to the greatest extent. DETAILED DESCRIPTION

[0050] The preparation method of the above-mentioned carbon nanotube-based fluid loss reducer is described in detail below through a specific implementation method.

[0051] In each embodiment of the present invention, the specific information of the reagents used is as follows:

[0052] γ-Aminopropyltrimethoxysilane was purchased from Hubei Jusheng Technology Co., Ltd.;

[0053] Hydroxylated multi-walled carbon nanotubes were purchased from Shanghai Kelaman Reagent Co., Ltd.;

[0054] Ethanol was purchased from Shandong Xinheng Chemical Co., Ltd.;

[0055] Sodium hydroxide was purchased from Jinan Huifengda Chemical Co., Ltd.;

[0056] Sodium dodecyl sulfate was purchased from Zhengzhou Alpha Chemical Co., Ltd.;

[0057] Sodium vinylbenzene sulfonate was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0058] N-vinylpyrrolidone was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0059] Trifluoroethyl methacrylate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0060] Ammonia water was purchased from Shandong Yukang Chemical Co., Ltd.;

[0061] Potassium persulfate was purchased from Jinan Jinhao Chemical Co., Ltd.;

[0062] 3-Aminopropyltriethoxysilane was purchased from Hubei Jusheng Technology Co., Ltd.;

[0063] 2-Acrylamido-2-methylpropanesulfonic acid was purchased from Tianmen Hengchang Chemical Co., Ltd.;

[0064] 5-vinyl-2-pyrrolidone was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0065] Azobisisobutyronitrile was purchased from Jinan Huifengda Chemical Co., Ltd.

[0066] γ-(2,3-Epoxypropyloxy)propyltrimethoxysilane was purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.;

[0067] 4-Vinylpyridine was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0068] Hexafluorobutyl methacrylate was purchased from Zhengzhou Alpha Chemical Co., Ltd.

[0069] Example 1

[0070] Into a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, a mixed solvent of 100 mL of ethanol and 20 mL of deionized water was added, the pH of the mixed solvent was adjusted to 7 with sodium hydroxide, 5 g of γ-aminopropyltrimethoxysilane (KH540) was added, and ultrasonic dispersion was performed at room temperature for 1 h. After sufficient hydrolysis, 1 g of hydroxylated multi-walled carbon nanotubes (20 nm) was added, and the mixture was stirred and mixed at 800 rpm / min. The water bath was heated to 40°C, the reaction was carried out for 1 h, and the mixture was repeatedly washed with ethanol. Then, the mixture was placed in an oven at 80°C and dried for 4 h to obtain modified multi-walled carbon nanotubes.

[0071] In a nitrogen atmosphere, 0.6 g of sodium dodecyl sulfonate (ABS) was dissolved in 50 mL of deionized water, and 5 g of sodium vinylbenzene sulfonate, 3 g of N-vinyl pyrrolidone, and 0.5 g of trifluoroethyl methacrylate were added and stirred thoroughly to obtain a pre-emulsion.

[0072] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, 1 g of modified multi-walled carbon nanotubes was dispersed in 100 mL of anhydrous ethanol, a pre-emulsified liquid was added, the pH value of the solution was adjusted to 7 with aqueous ammonia, 0.3 g of potassium persulfate was added, and the mixture was heated in a water bath at 60 ° C with a mechanical stirring speed of 1000 rpm / min. After reacting for 3 hours, the product was repeatedly filtered and washed with anhydrous ethanol, and then dried at 80 ° C for 8 hours to obtain a carbon nanotube-based filtrate reducer.

[0073] Example 2

[0074] A mixed solvent of 100 mL of ethanol and 20 mL of deionized water was added to a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, and the pH of the mixed solvent was adjusted to 9 with sodium hydroxide, and 7 g of 3-aminopropyltriethoxysilane (KH550) was added. Ultrasonic dispersion was performed at room temperature for 2 h. After sufficient hydrolysis, 3 g of hydroxylated multi-walled carbon nanotubes (110 nm) were added, and the mixture was stirred at 1000 rpm / min, and the water bath was heated to 50 ° C. The reaction was performed for 2 h, and the mixture was repeatedly washed with ethanol. Then, the mixture was placed in an oven at 80 ° C. and dried for 6 h to obtain modified multi-walled carbon nanotubes.

[0075] In a nitrogen atmosphere, 1.0 g of sodium dodecyl sulfonate (ABS) was dissolved in 80 mL of deionized water, and 7 g of 2-acrylamido-2-methylpropanesulfonic acid, 4 g of 5-vinyl-2-pyrrolidone and 1 g of trifluoroethyl methacrylate were added and stirred thoroughly to obtain a pre-emulsion.

[0076] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, 2 g of modified multi-walled carbon nanotubes were dispersed in 100 mL of anhydrous ethanol, and a pre-emulsified liquid was added. The pH value of the solution was adjusted to 8 with aqueous ammonia, and 0.4 g of azobisisobutyronitrile was added. The solution was heated in a water bath at 70 ° C with a mechanical stirring speed of 1200 rpm / min. After reacting for 4 hours, the product was repeatedly filtered and washed with anhydrous ethanol, and then dried at 80 ° C for 6 hours to obtain a carbon nanotube-based filtrate reducer.

[0077] Example 3

[0078] A mixed solvent of 100 mL of ethanol and 20 mL of deionized water was added to a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a heating device. The pH of the mixed solvent was adjusted to 8 with sodium hydroxide, and 10 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) was added. Ultrasonic dispersion was performed at room temperature for 3 hours. After sufficient hydrolysis, 5 g of hydroxylated multi-walled carbon nanotubes (280 nm) were added. The mixture was stirred at 1000 rpm / min, and the water bath was heated to 60°C for 3 hours. The mixture was repeatedly washed with ethanol. The mixture was then placed in an oven at 80°C and dried for 8 hours to obtain modified multi-walled carbon nanotubes.

[0079] In a nitrogen atmosphere, 1.5 g of sodium dodecyl sulfonate (ABS) was dissolved in 150 mL of deionized water, and 10 g of sodium vinylbenzene sulfonate, 5 g of 4-vinylpyridine, and 2 g of hexafluorobutyl methacrylate were added and dissolved in 150 mL of an emulsifier to obtain a pre-emulsion.

[0080] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, 3 g of modified multi-walled carbon nanotubes were dispersed in 100 mL of anhydrous ethanol, and a pre-emulsified liquid was added. The pH value of the solution was adjusted to 9 with aqueous ammonia, and 0.6 g of potassium persulfate was added. The solution was heated in a water bath at 80 ° C with a mechanical stirring speed of 1100 rpm / min. After reacting for 6 hours, the product was repeatedly filtered and washed with anhydrous ethanol, and then dried at 80 ° C for 8 hours to obtain a carbon nanotube-based filtrate reducer.

[0081] Comparative Example A

[0082] The difference from Example 2 is that no modified multi-walled carbon nanotubes are added, that is:

[0083] In a nitrogen atmosphere, 1.0 g of sodium dodecyl sulfonate (ABS) was dissolved in 80 mL of deionized water, and 7 g of 2-acrylamido-2-methylpropanesulfonic acid, 4 g of 5-vinyl-2-pyrrolidone and 1 g of trifluoroethyl methacrylate were added and stirred thoroughly to obtain a pre-emulsion.

[0084] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer and a heating device, add the pre-emulsion, adjust the pH value of the solution to 8 with aqueous ammonia, add 0.4 g of azobisisobutyronitrile, heat in a water bath, and mechanically stir at 70°C at a speed of 1200 rpm / min. After reacting for 4 hours, the product is repeatedly filtered and washed with anhydrous ethanol, and then dried at 80°C for 6 hours to obtain a polymer filtrate reducer.

[0085] In order to further illustrate the effect of the carbon nanotube-based fluid loss reducer of the present invention, the performance of the fluid loss reducers in Examples 1 to 3 and Comparative Example A was tested.

[0086] 1. Particle size test of carbon nanotube fluid loss reducer

[0087] The particle size of the carbon nanotube-based fluid loss reducer was tested using a Bettersize 2000 laser particle size distribution instrument. The particle size test results of the fluid loss reducers prepared in Examples 1 to 3 and Comparative Example A are shown in Table 1. It can be seen from the examples that the particle size of the fluid loss reducer of the present invention can be prepared according to the needs to prepare fluid loss reducer particles of corresponding particle sizes. The particle size of the fluid loss reducer prepared in Comparative Example A is relatively large, mainly because in the reaction process, there is no steric hindrance of rigid particles, the polymer molecules are easy to generate long chain structures, and the molecular particle size formed is large.

[0088] Table 1 Test results of particle size of fluid loss reducer of Examples 1 to 3 and Comparative Example A

[0089] Example Median particle size / nm Example 1 83 Example 2 352 Example 3 758 Comparative Example A 1567

[0090] 2. Temperature resistance, salt resistance and fluid loss reduction of carbon nanotube-based fluid loss reducers

[0091] Evaluation of thermal wall resistance: (1) 2% of the filtrate reducers of Examples 1-3 and Comparative Example A were added to 4% pre-bentonite slurry, and stirred until the filtrate reducers were completely dissolved to form a drilling fluid system; (2) The filtrate loss of the drilling fluid system was measured at room temperature using a ZNN-D6 electric six-speed rotary viscometer and an SD-3 medium-pressure filtrate meter; after the measurement, the drilling fluid system was transferred to an XGRL-4A high-temperature roller furnace produced by Qingdao Haitongda Special Instrument Factory, aged at 180°C for 16 hours, and then returned to room temperature after aging; (3) The filtrate loss of the aged drilling fluid system was measured at room temperature, and the changes in the filtrate volume of the drilling fluid system before and after aging were compared, and the change in the filtrate volume was used as an indicator for evaluating the thermal resistance and filtrate loss reduction of the polymer. (4) The weight of the filter cake on the filter paper after API loss test can be used to reflect the wall-forming property. The specific experimental steps are as follows: take the filter cake after API loss test, scrape the filter cake off the filter paper, dry the scraped filter cake in a vacuum oven, and weigh the filter cake.

[0092] Table 2 Test results of temperature resistance and fluid loss of Examples 1 to 3 and Comparative Example A

[0093]

[0094]

[0095] From the data in Table 2, it can be seen that the carbon nanotube-based fluid loss agent of the present invention has good temperature resistance before and after aging at 180°C, and the fluid loss amount does not change much before and after aging. However, the fluid loss amount of comparative example A changes greatly before and after aging, and the mud cake is thick. The main reason is that the long-chain polymer fluid loss agent has no rigid structure, and the mud cake formed is of poor quality. Under the action of high temperature, the chain breaks and the performance deteriorates further.

[0096] Evaluation of temperature and salt resistance and wall-building property: (1) 2% of the fluid loss reducers of Examples 1-3 and Comparative Example A were added to 4% pre-bentonite slurry, stirred until the fluid loss reducers were completely dissolved, and then 20% sodium chloride was added and stirred for 40 minutes to form a drilling fluid system; (2) The fluid loss of the drilling fluid system was measured at room temperature using a ZNN-D6 electric six-speed rotary viscometer and an SD-3 medium-pressure filter loss meter; after the measurement, the drilling fluid system was transferred to an XGRL-4A high-temperature roller furnace produced by Qingdao Haitongda Special Instrument Factory and heated at 180 ℃ for 16 hours and then aged to room temperature; (3) measuring the filtration loss of the aged drilling fluid system at room temperature, comparing the change in the filtrate volume of the drilling fluid system before and after aging, and taking the change in the filtrate volume as an indicator for evaluating the polymer's resistance to temperature and salt and filtration loss; (4) testing the weight of the filter cake on the filter paper after API filtration loss to further reflect the wall-forming property. The specific experimental steps are as follows: taking the filter cake after the API filtration loss test, scraping the filter cake from the filter paper, drying the scraped filter cake in a vacuum oven, and weighing the filter cake.

[0097] Table 3 Test results of temperature and salt resistance of examples 1 to 3 and comparative example A

[0098]

[0099]

[0100] From the data in Table 3, it can be seen that the carbon nanotube-based fluid loss reducer of the present invention has little change in the fluid loss amount compared with Table 2 before and after aging at 180°C after adding 20% ​​NaCl, and still maintains good water loss and wall-building properties, indicating that the fluid loss reducer of the present invention can resist 20% NaCl. However, the mud cake of Comparative Example A before and after aging has poor quality, large fluid loss, and thick mud cake. The main reason is that in the high-concentration salt solution, before aging, the long-chain structure polymer molecules cannot be fully extended, and some polymer molecules are in a curled state. Under the action of high temperature, the long chain breaks, the curled molecules further clump together, and the polymer performance deteriorates sharply.

[0101] The following is a detailed description of the method for preparing high temperature resistant clay-free low solid phase water-based drilling fluid using samples of Examples 1 to 3 through a specific implementation method.

[0102] In each embodiment of the present invention, the specific information of the reagents used is as follows:

[0103] Xanthan gum was purchased from Shandong Wankang Biotechnology Co., Ltd.;

[0104] Guar gum was purchased from Shandong Wankang Biotechnology Co., Ltd.;

[0105] Wenlunjiao was purchased from Shandong Wankang Biotechnology Co., Ltd.;

[0106] Magnesium oxide was purchased from Jinan Huifengda Chemical Co., Ltd.;

[0107] Sodium hydroxide was purchased from Jinan Huifengda Chemical Co., Ltd.;

[0108] Potassium hydroxide was purchased from Jinan Huifengda Chemical Co., Ltd.;

[0109] Sodium formate, purchased from Hubei Jusheng Technology Co., Ltd.;

[0110] Sodium sulfite was purchased from Hubei Jusheng Technology Co., Ltd.;

[0111] Thiourea, purchased from Shandong Xinheng Chemical Co., Ltd.;

[0112] Potassium formate, purchased from Hubei Jusheng Technology Co., Ltd.;

[0113] Sodium citrate, purchased from Hubei Jusheng Technology Co., Ltd.;

[0114] Calcium carbonate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0115] Example 4

[0116] A high temperature resistant clay-free low solid phase water-based drilling fluid, the selection of each raw material component and its relative application amount are shown in Table 4 and Table 5, and is prepared according to the following steps:

[0117] Take 100g of water, add pH regulator, viscosity enhancer, fluid loss reducer, shielding temporary plugging agent, organic salt and deoxidizer in sequence, stir evenly at a speed of 10000r / min to obtain high temperature resistant clay-free low solid phase water-based drilling fluid.

[0118] Examples 5 to 8 are high temperature resistant clay-free low solid water-based drilling fluids. The difference from Example 4 is that the selection of each raw material component and its relative dosage are shown in Tables 4 and 5.

[0119] Table 4 Amount of solid-free drilling fluid raw materials used in Examples 4 to 8 (g)

[0120]

[0121] Table 5 Selection and mass fractions of specific components of the solid-free drilling fluid raw materials in Table 4 (based on 100 parts)

[0122]

[0123] Comparative Example

[0124] Comparative Example 1 is a solid-free drilling fluid, which is different from Example 7 in that an equal amount of high-viscosity polyanionic cellulose is used in the viscosity increasing agent to replace the xanthan gum, guar gum and vinblastine gum of the present invention.

[0125] Comparative Example 2 is a solid-free drilling fluid, which is different from Example 7 in that an equal amount of modified starch is used in the fluid loss reducer to replace the carbon nanotube-based fluid loss reducer of the present invention.

[0126] Comparative Example 3 is a solid-free drilling fluid, which is different from Example 7 in that the mesh size of the fluid loss reducer is 300nm-500nm instead of Example 7 which is compounded with different mesh sizes.

[0127] Comparative Example 4 is a solid-free drilling fluid, which is different from Example 7 in that the mesh size of the fluid loss reducer is 300nm-500nm, and the mesh size of the shielding temporary plugging agent is 1200-1500 mesh.

[0128] Solid-free drilling fluid performance test method: Test the density, rheology and filtration loss (FL) of solid-free drilling fluid after aging at 180℃ for 16h. API ), the test results are shown in Table 6.

[0129] Table 6 Test results of solid-free drilling fluid performance

[0130]

[0131] As can be seen from Table 6, Examples 4 to 8 of the present invention still maintain good rheological properties after aging at 180°C for 16 hours, and can effectively reduce the filtration loss of drilling fluid compared with Comparative Examples 1 to 4. The reason may be that, compared with Comparative Examples 1 to 4, the viscosity enhancer, filtration loss reducer, and shielding temporary plugging agent added in the present invention are conducive to forming a dense filter cake and reducing the penetration of water in the drilling fluid.

[0132] Any numerical value mentioned in the present invention includes all values ​​that increase by one unit each time from the lowest value to the highest value if there is only an interval of two units between any minimum value and any maximum value. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed lowest and highest values ​​are considered to have been disclosed.

[0133] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A carbon nanotube-based fluid loss reducer, It is characterized in that The carbon nanotube fluid loss reducer is prepared by polymerizing raw materials including hydroxylated multi-walled carbon nanotubes, amino-containing silane coupling agents, sulfonate monomers, alkenyl polycyclic monomers, and fluorine-containing short carbon chain acrylate monomers.

2. The carbon nanotube-based fluid loss reducer according to claim 1, It is characterized in that The amino-containing silane coupling agent is selected from any one of γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane; And / or, the sulfonate monomer is selected from any one of sodium p-vinylbenzenesulfonate and 2-acrylamido-2-methylpropanesulfonic acid; And / or, the alkenyl polycyclic monomer is selected from any one of 1-vinyl-2-pyrrolidone, 5-vinyl-2-pyrrolidone, and 4-vinylpyridine; And / or, the perfluorinated short carbon chain acrylate monomer is selected from any one of trifluoroethyl methacrylate and hexafluorobutyl methacrylate; And / or, the particle size of the hydroxylated multi-walled carbon nanotubes is 10 to 300 nm.

3. The carbon nanotube-based fluid loss reducer according to claim 1 or 2, It is characterized in that The particle size of the carbon nanotube-based fluid loss reducer is 50nm-1um.

4. A method for preparing the carbon nanotube-based fluid loss additive according to any one of claims 1 to 3, It is characterized in that The following steps are involved: S1: in a mixed solvent, reacting hydroxylated multi-walled carbon nanotubes with an amino-containing silane coupling agent to obtain modified multi-walled carbon nanotubes; S2: dissolving sulfonate monomers, alkenyl polycyclic monomers, and fluorine-containing short carbon chain acrylate monomers in an aqueous emulsifier solution, and polymerizing them with the modified multi-walled carbon nanotubes under the action of an initiator to obtain a carbon nanotube-based fluid loss reducer.

5. The preparation method according to claim 4, It is characterized in that In step S1, the mass ratio of the hydroxylated multi-walled carbon nanotubes to the amino-containing silane coupling agent is 1-5:3-10; And / or, in step S1, the mixed solvent is ethanol and deionized water, and / or the volume ratio of the ethanol to the deionized water is (3-8):(0.5-1), preferably 5:1; And / or, in step S2, the mass ratio of the sulfonate monomer, the alkenyl polycyclic monomer, the fluorine-containing short carbon chain monomer, and the modified multi-walled carbon nanotube is 5-10:2-5:0.5-2:1-3.

6. The preparation method according to claim 4 or 5, It is characterized in that In step S2, the emulsifier is selected from sodium dodecyl sulfate; And / or, the amount of the emulsifier is 0.05-0.1 of the total amount of the monomers used, and the total amount of the monomers is the total mass of the sulfonate monomers, the alkenyl polycyclic monomers, and the fluorinated short carbon chain acrylate monomers; and / or, the mass ratio of the emulsifier to water in the emulsifier aqueous solution is 1:(50-100); And / or, the initiator is potassium persulfate or azobisisobutyronitrile; And / or, the amount of the initiator is 0.02-0.04 of the total amount of the monomers used, and the total amount of the monomers is the total mass of the sulfonate monomers, the alkenyl polycyclic monomers, and the fluorine-containing short carbon chain acrylate monomers.

7. The preparation method according to any one of claims 4 to 6, It is characterized in that In the step S1, the modification temperature is 40-60°C and the modification time is 1-3h; And / or, in step S2, the polymerization temperature is 50-80° C., and the polymerization time is 2-6 hours.

8. A high temperature resistant, clay-free, low solid phase water-based drilling fluid. It is characterized in that Including the following raw materials by mass: Fresh water: 100 parts; pH regulator: 0.2-0.5 parts; Thickener: 1-2 parts; Fluid loss reducer: 0.5-2 parts; Shielding temporary plugging agent: 3 to 6 parts; Organic salt: 20-200 parts; Deoxidizer: 0.5-2 parts; Wherein, the fluid loss reducer is selected from at least one of the carbon nanotube-based fluid loss reducer described in any one of claims 1 to 3 and the carbon nanotube-based fluid loss reducer prepared by the preparation method described in any one of claims 4 to 7.

9. The high temperature resistant clay-free low solid phase water-based drilling fluid according to claim 8, It is characterized in that The fluid loss reducer comprises a variety of particle sizes, and the mass ratio of the different particle sizes is 50-100nm: 300nm-500nm: 700nm-1um=10-30: 10-40: 50-60.

10. The high temperature resistant clay-free low solid phase water-based drilling fluid according to claim 8 or 9, It is characterized in that The pH regulator is selected from one of magnesium oxide, sodium hydroxide and potassium hydroxide; And / or, the organic salt is selected from one or more of sodium formate and potassium formate; And / or, the temporary shielding plugging agent is ultrafine calcium carbonate compounded with different mesh sizes, and the different mesh sizes are calculated by mass ratio of 500-600 mesh: 1200-1500 mesh: 2000-2500 mesh = 30-60: 20-40: 10-30; And / or, the deoxidizer is selected from a mixture of one or more of sulfites, thioureas and citrates; And / or, the mass of the viscosity enhancer is 100 parts, including 30 to 50 parts of xanthan gum, 10 to 30 parts of guar gum and 20 to 40 parts of wenlun gum.

Citation Information

Patent Citations

  • Salt resistant high-temperature resistant solid-free environment-friendly well drilling and completing integrated working fluid

    CN102031094A

  • High-temperature-resistant degradable solid-free drilling fluid and preparation method thereof

    CN113861951A

  • Flexible-outside rigid-inside multi-walled carbon nanotube nano plugging agent and oil-based drilling fluid

    CN114214047A

  • Electrically conductive wellbore fluids and methods of use

    CN104870597A

  • High-temperature-resistant salt-resistant organic silicon filtrate reducer as well as preparation method and application thereof

    CN114989348A

Cited By

  • Soil-free phase reservoir protection water-based drilling fluid as well as preparation method and application thereof

    CN121427508A